Children’s literature as a means of disability awareness and ICT’s role - Manola, Maria; Vouglanis, Taxiarchis; Maniou, Fotini; Driga, Anna Maria (Eximia, 2023)
People construct the image of disability through myths, anecdotes, stories and jokes that circulate in a given historical and cultural period. Cultural institutions, however, silence the ways in which such forms of discourse perpetuate social perceptions and assumptions. The deviation of individuals from the dominant normative standards is the main cause for their social marginalization and the shrinking of their human status. Literature has always been a powerful carrier of ideological messages that sometimes have the objective of consolidating and sometimes revising the dominant social structures and the categorization of vulnerable groups within them. This also applies to disability. The way it is portrayed through children’s literature is an important means of raising their awareness towards it so that prejudices and stereotypes do not prevail.